Move Along: Community-based Research into the Policing of Sex Work in Washington, D.C - Saunders, Penelope (Social justice, 2010)
The article reports on a research effort organized by the U.S. organization known as the Alliance for a Safe and Diverse D.C. which examined the perceived harms deriving from the criminalization of sex work in Washington, D.C. This study pertains to several anti-prostitution laws that were passed in D.C. during 2005 that expand the powers of police and other regulatory authorities to reduce street- and place-based sex work. The described research project was organized partly due to reports of police abuse but also to serve as a tool that could help community members resist police brutality and oppression.